The Effect of Extension with Audio Visual Method on The Improvement of Knowledge Levels and Attitude of The Use of Borax In The Making of Gendar Crackers in Family Households - Dyah Suryani; Wibowo Wibowo (Aloha International Journal of Health Advancement (AIJHA), 2019)
Background: Food is one of the basic important of human needs. Since the mid-20th century, the role of food additives, particularly preservatives are becoming increasingly important in line with advances in production technology of synthetic BTP (food additives). The use of BTP often adverse effects on health. Some of the causes were the use of non-organic materials due to economic reasons. The lower public's knowledge about quality and safety of food led to rampant cases of food poisoning. This compounded with various kinds of food additives (BTP) are derived from chemical products and its derivatives. Cracker was one of snack that much-loved by the majority of Indonesian people. On making of Crackers both the traditional and the modern are often added borax as a food additive that was felt to be more savory crackers and crunchy. This research aimed to examine the influence of counseling with audio-visual method on the improvement of knowledge and attitude of use borax on making gendar crackers family households in Kategan, Patalan, Jetis, Bantul, Special Region of Yogyakarta Province. Methods: This research used quasi experiment type with the design of one group pretest - posttest. The samples were housewives in the Kategan, Patalan, Jetis, Bantul. Results: There was a difference of housewife’s knowledge in Kategan on the use of borax on making gendar crackers between before and after counseling with audio-visual methods which seen by a mean value of 6.64 pre-test and 6.92 for post-test average with -1.238 as mean difference. Based on the results of Wilcoxon test obtained p-value of 0.216 (H0 was accepted). While the mean, obtained on the attitude of the pre-test of 10.28 and the mean of post-test of 11.19 with a mean difference of -2.018. The p-value was 0.044 (H0 was rejected). Conclusion: There was no effect of counseling with the use of audio-visual methods in use of borax on making gendar crackers on the knowledge. Whereas there was influence of counseling with the use of audio-visual methods in the use of borax on making gendar crackers on the attitude. Keywords: knowledge, attitudes, audio visual, borax